Statistical modelling of factors influencing the agricultural land market in Ukraine - Lazebnyk, Iuliia; Korepanov, Oleksiy; Chala, Tetyana; Korepanov, Georgii; Chernenko, Daryna; Plumite, Uldis; Komlieva, Maryna; Лазебник, Юлія Олександрівна; Корепанов, Олексій Сергійович; Чала, Тетяна Георгіївна; Корепанов, Георгій Сергійович; Черненко, Дарина Ігорівна; et al. (Latvia, Riga: Institute of Physical Energetics, 2022)
To make informed decisions, modern society, like modern business, must operate with adequate information about many complex interrelated aspects of its activities. Land use is only one of such aspects. Agricultural lands are of particular importance today. Land data are needed to analyse environmental processes, as well as end unsystematic, uncontrolled use of agricultural land, environmental degradation, destruction of important wetlands, loss of fish diversity and destruction of wildlife habitats. To solve these problems, it is advisable to conduct regular analysis and evaluation of land resources, justification and analysis of factors influencing the agricultural land market in the country. The tasks were solved using multidimensional statistical methods, in particular, factor analysis, which helped to get rid of subjectivity in the choice of factors influencing the market under study. Based on the model of influence of factors on the national market of agricultural land in Ukraine, six main factors were identified, the most influential of which were the components of agricultural development (first factor) and, to a lesser extent, the component of vegetable production and yield (fourth factor). The interrelationships and the degree of influence of the selected factors on the main indicators of the agricultural land market, namely, on the area of purchase and sale plots, the price of purchase and sale plots, and the number of transactions were also analysed.

Для прийняття обґрунтованих рішень сучасне суспільство, як і сучасний бізнес, повинно оперувати адекватною інформацією про багато складних взаємопов'язаних аспектів своєї діяльності. Землекористування – лише один із таких аспектів. Сільськогосподарські угіддя мають особливе значення сьогодні. Дані про землю необхідні для аналізу екологічних процесів, а також для припинення безсистемного, неконтрольованого використання сільськогосподарських угідь, деградації навколишнього середовища, знищення важливих водно-болотних угідь, втрати різноманітності риб та знищення середовищ існування диких тварин. Для вирішення цих проблем доцільно проводити регулярний аналіз та оцінку земельних ресурсів, обґрунтування та аналіз факторів, що впливають на ринок сільськогосподарських земель у країні. Завдання вирішувалися за допомогою багатовимірних статистичних методів, зокрема факторного аналізу, який допоміг позбутися суб'єктивізму у виборі факторів, що впливають на досліджуваний ринок. На основі моделі впливу факторів на національний ринок сільськогосподарських земель в Україні було визначено шість основних факторів, найбільш впливовими з яких були компоненти розвитку сільського господарства (перший фактор) та, меншою мірою, компонент виробництва та врожайності овочів (четвертий фактор). Також було проаналізовано взаємозв'язки та ступінь впливу обраних факторів на основні показники ринку сільськогосподарських земель, а саме: на площу ділянок купівлі-продажу, ціну ділянок купівлі-продажу та кількість угод.
Статистичне моделювання факторів, що впливають на ринок сільськогосподарських земель в Україні
Keywords: SOCIAL SCIENCES::Business and economics; SOCIAL SCIENCES::Statistics, computer and systems science::Statistics; agricultural lands; analysis of the development; factor analysis; land potential; land resources; method of principal components; метод головних компонент; земельні ресурси; сільськогосподарські угіддя; аналіз розвитку; факторний аналіз; земельний потенціал